Relationship and Interaction between Project Management and Business Strategy - Slavova, Irena (Research Papers, 2011)
The study explores the relationship and interaction between project management and business strategy of the organization. Based on a research among the scientific and applied developments in this area, this paper clarifies the nature of the bilateral influence between project management and business strategy. The question is how project management can be consistent with the strategic requirements that the organization has identified and the opposite impact that projects under implementation may have taken on business strategy.The study focuses on the detailed process to achieve an alignment between project management and business strategy, including strategic planning, project portfolio management and project life cycle management. A ground is given on the crucial role of managing a portfolio of projects as a mediating process for the alignment between project management and business strategy of organization. Emphasis is placed on the use of strategic tools in the management of portfolio of projects: a strategic approach to selecting projects, different stages in the process of assessing projects and their prioritization, as well as performing periodic evaluation of the correlation between management of the portfolio of projects and business strategy of organization.